Manual of use and interpretation of pathology tests - McPherson, Jean (Royal College of Pathologists of Australasia, 1997)
This book is aim to produce a comprehensive manual to guide clinicals in the selection of appropriate pathology investigations and to assists in the interelations of pathology results.